Nizkoenergijska polarizirana svetlobna terapija - Kampič, Petra (Rehabilitacija (Ljubljana), 2010)
Low-energy polarised light therapy is reviewed, which is used for reducing inflammation and speeding-up healing of injured soft tissues. Findings published in English language literature since 2000 are summarised, whereby the following bibliographic databases were searched: PubMed, MEDLINE, Cochrane Central Register of Controlled Trials (CCTR), Cochrane Database of Systematic Reviews (CDRS), Database of Abstract of Reviews of Effects (DARE), EMBASE, Science Direct, Trip Database Plus, Cumulative Index to Nursing &Allied Health Literature (CINAHL), and PEDro. Secondary studies (meta-analyses) are summarised as well as quantitative primary studies (randomised controlled trials). They assessed effects of low-energy polarised light therapy in patients with burns, carpal tunnel syndrome, lateral epicondylitis, postoperative wounds, pressure ulcers and neuropathic pain. The published findings demonstrate that therapy with polarised light is safe, but there is a lack of high-quality studies on efficiency. The literature suggests that the polarised light therapy is most efficient in treatment of venous ulceration and skin transplants in wounds.
Keywords: fototerapija; svetloba; therapy; zdravljenje